2019
DOI: 10.1186/s12885-019-5632-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic predictors of metastasis of different regional lymph nodes in patients intraoperatively diagnosed with stage-I non-small cell lung cancer

Abstract: Background Selection of the best lymph node for dissection is a controversial topic in clinical stage-I non-small cell lung cancer (NSCLC). Here, we sought to identify the clinicopathologic predictors of regional lymph node metastasis in patients intraoperatively diagnosed with stage-I NSCLC. Methods A retrospective review of 595 patients intraoperatively diagnosed as stage I non-small-cell lung cancer who underwent lobectomy with complete lymph node dissection was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Historically, pulmonary resection with lymphadenectomy is the standard treatment for NSCLC patients ( 6 ). It is recommended even for the early stage of NSCLC patients—T1N0M0 patients, which may because occult lymph node metastasis and false-negative lymph nodes exist ( 7 , 8 ). However, the optimal number of regional lymph nodes removed (LNRs) during surgery has remained debated all the time for the N0 NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, pulmonary resection with lymphadenectomy is the standard treatment for NSCLC patients ( 6 ). It is recommended even for the early stage of NSCLC patients—T1N0M0 patients, which may because occult lymph node metastasis and false-negative lymph nodes exist ( 7 , 8 ). However, the optimal number of regional lymph nodes removed (LNRs) during surgery has remained debated all the time for the N0 NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pani et al found that histologic subtypes could be related to lymph node status (4). Another similar study suggested different LND strategy for different combination of various clinicopathological features and CEA concentration and albumin level (30). These studies used uni-and multivariate analysis to reveal clinicopathological predictors for different LNM patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Pani et al found that histologic subtypes could be related to lymph node status [34]. Another similar study suggested different lymph node dissection strategy for different combination of various clinicopathological features and CEA concentration and albumin level [35]. These studies used uni-and multivariate analysis to reveal clinicopathological predictors for different LNM patterns.…”
Section: Discussionmentioning
confidence: 99%